2022
DOI: 10.1055/s-0041-1730889
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Outcomes of Advanced Cholangiocarcinoma: A Single-Center Experience from India

Abstract: Background Survival data for patients with advanced cholangiocarcinoma are very sparse in India. We performed this study to find the median overall survival of patients with advanced cholangiocarcinoma and to identify prognostic factors for survival. Methods This is a retrospective study of 30 patients with inoperable and metastatic cholangiocarcinoma treated with cisplatin and gemcitabine chemotherapy. Overall survival was estimated by the Kaplan–Meier method. Univariate and multivariate analyses we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…Age is an unsurprising factor given the constitutional changes of aging and general trends of morbidity and mortality. Previous studies have also shown serum albumin level, which may indicate nutritional status, and serum CA 19-9, which may indicate tumor burden, to be prognostic for cholangiocarcinoma [ 21 - 23 ]. CA 19-9 was predictive of survival after resection of extrahepatic cholangiocarcinoma, ranging in cut-off value from 30 to 300 U/mL.…”
Section: Discussionmentioning
confidence: 99%
“…Age is an unsurprising factor given the constitutional changes of aging and general trends of morbidity and mortality. Previous studies have also shown serum albumin level, which may indicate nutritional status, and serum CA 19-9, which may indicate tumor burden, to be prognostic for cholangiocarcinoma [ 21 - 23 ]. CA 19-9 was predictive of survival after resection of extrahepatic cholangiocarcinoma, ranging in cut-off value from 30 to 300 U/mL.…”
Section: Discussionmentioning
confidence: 99%
“…The landmark ABC-02 trial demonstrated a survival benefit with GemCis compared to gemcitabine alone, making it the standard first-line treatment [ 5 ]. However, despite this advancement, the prognosis for metastatic BTC remains dismal, with a median survival of less than a year [ 5 , 6 ]. This underscores the urgent need for more effective therapies for this challenging disease.…”
Section: Introductionmentioning
confidence: 99%